(untitled) (Ustozlar uchun, 2025)
This article explores the significance of developing students’ functional literacy in accordance with the principles of the PISA (Programme for International Student Assessment) international research. Functional literacy refers to learners’ ability to apply knowledge and skills in real-life contexts rather than relying solely on theoretical understanding. The paper discusses the components of functional literacy assessed by PISA—reading, mathematical, and scientific literacy—and examines effective pedagogical strategies for improving these competencies. Challenges faced by educators in preparing students for PISA-like tasks are also analyzed, along with practical recommendations to enhance learning outcomes. The study concludes that focusing on functional literacy helps students become more independent, critical thinkers, and active participants in modern society.